PENYELESAIAN TUNGGAKAN REKENING AIR PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA PADANG OLEH JAKSA SELAKU PENGACARA NEGARA (Studi pada Kejaksaan Negeri Padang) - Hartato, Depi (Universitas Ekasakti, 2020)
This research examines the implementation of the Settlement of Water Account Arrears at the Padang City Water Company (PDAM) by the Prosecutor as State Lawyer (Study at the Padang State Prosecutor's Office). This research is a descriptive analytical study. The approach method used in this research is juridical normative with an empirical approach, using secondary and primary data collected through literature and field studies with data collection techniques through interviews and documentation. The results showed that: PDAM has billed but not getting the maximum results, Kejari Padang is experienced in helping to settle arrears for customers of PT Permodalan Nasional Madani (Persero) Tbk and PDAM continues to cooperate with Kejari Padang. Second, the settlement of water account arrears for PDAM Kota Padang customers by the Prosecutor as the State Attorney is that the PDAM contacts the Padang Prosecutor's Office and coordinates regarding the material of the problem so that JPN digs up the problem, if it enters the civil realm then the PDAM makes a Special Power of Attorney as the basis for JPN to call customers who are in default, Some customers who have been summoned have paid in full and some have paid in installments (made a full payment statement), if the agreement cannot be reached, JPN will make a report to the leadership and the leadership to report to the PDAM that the resolution of the problem can be done through a litigation process.